CORPORATE INJURY AS A CRIME AGAINST LIFE AND HUMAN HEALTH UNDER THE CRIMINAL LAW OF UKRAINE - Katerynchuk, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Review of the monograph "Personal injury as a crime against human life and health under the criminal law of Ukraine" V.V. Shablistogo and V.Yu. Kolomiets